Outcomes of Surgical Treatment of Peripheral Neuromas of the Hand and Forearm - El-Gammal, Yousif Tarek; Cardenas-Mateus, Laura; Tsai, Tsu Min (Journal of Brachial Plexus and Peripheral Nerve Injury, 2023)
The choice of a specific technique for surgical treatment of neuromas remains a problem. The purpose of this study is to determine the overall effectiveness of surgery as well as to find out whether certain surgical procedures are more effective than others. Twenty-nine patients operated between 1998 and 2018 and followed for at least 12 months were reviewed. Clinical assessment included the identification of a pre- and postoperative Tinel sign, pain visual analog score, two-point discrimination (2PD), and grip strength. Mechanisms of injury included clean lacerations (11), crush injuries (11), and other trauma or surgery (7). Mean time from presentation to surgery was 9 months. Seven surgical procedures involving excision in 10 patients and excision and nerve repair in 19 patients were performed. Pain score improved from an average of 7.1 ± 2.3 to 1.8 ± 1.7 with 27 patients (93%) reporting mild or no postoperative pain. Nine patients complained of residual scar hypersensitivity and six patients had residual positive Tinel. No patient required an additional surgical procedure. 2PD improved from an average of 9.6 ± 4.0 to 6.8 ± 1.0. The improvement of pain score and 2PD was statistically significant. Nerve repair resulted in marginally better outcomes, in terms of 2PD and grip strength recovery, than excision alone. The mechanism of injury, zone of involvement, time to intervention, or length of follow-up did not have an impact on the outcomes. Although patient numbers in this study are large in comparison to previous studies, larger patient numbers will allow for a multivariate analysis, which can be possible with a prospective multicenter trial.
Keywords: neuroma; resection; reconstruction